Gua Batu: Hunian Prasejarah di Pegunungan Meratus, Kalimantan Selatan - Nia Marniati Etie Fajari; Muhammad Wishnu Wibisono (Balai Arkeologi Yogyakarta, 2020)
Preliminary studies in the karst hills of the Meratus Mountains in Kotabaru Regency found rock-shelters and caves that were indicated to have traces of prehistoric dwellings. One of them is Batu Cave which is in Batangkulur village, Kelumpang Barat district. This article discusses the results of excavations carried out in Batu Cave in 2018. The problems raised on proof of occupancy and how human life in the past in Batu Cave. Archaeological data were obtained from excavations by using test-pit at two different locations. The excavation findings analyses are quantitative and qualitative. Quantitative analysis was carried out to find out the quantity of findings. The qualitative analysis includes an initial classification, which divides archeological data according to the type, form and style. The results show that Batu Cave are cave dwelling with living activities that rely on the surrounding resources. Exploitation of environmental resources is seen in the use of several types of terrestrial fauna and water as one of the main food sources. Various types of tools were made using rocks, as well as bones and shells.